Standardization Issues of Mobile Usability - Nacheva, Radka Valerieva (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The benefits of maintaining standards can be summarized from different perspectives: consumers, businesses, governments, economically. They inform and shape the products we buy, ensuring quality and safety. Standardizing in dynamic activities such as the development of mobile applications and devices can be not easy task. In this regard, the aim of the current paper is to revise some international standard towards usability problems of mobile user interfaces and to analyze the possibility of standardization of mobile usability.